Wisdom and narrative: dealing with complexity and judgement in translator education - J. Marais (Acta Theologica)
This article explores wisdom as concept to guide translator education in institutions of higher education. It uses the work of Paul Baltes to posit wisdom as the orchestration of mind and virtue for the common good. Wisdom then signifies the outcome of translator education. Narrative is a mode of communication that is able to foster wisdom. In this respect, the article elaborates on Baker’s use of narrative theory in translation studies. In conclusion certain aspects of education are suggested, which would enhance translators’ wisdom so that they may be able to judge ill-structured, complicated communication situations in order to enhance communication.